Review Paper on MSEEC: Energy Efficient Clustering Protocol in HWSN - Rana, Atul; Bala, Manju; Varsha, (International Journal of Computer Sciences and Engineering, 2025)
In Wireless Sensor Networks (WSNs), classical clustering protocols assume that all nodes are equipped with the same amount of energy. In addition, the extension to multi-level of SEEC is presented. The performance of the proposed protocol is examined and compared by existing homogeneous and heterogeneous protocols. Simulation results show that the proposed protocol provides a longer/more stability period, more energy efficiency and higher average throughput than the existing protocols